Mn < 2 + > ion doped enhanced upconversion red light emitting scandium aluminate and synthesis method thereof

By doping manganese ions in barium scandium aluminate, the red light emission efficiency of rare earth doped materials is improved, and the problem of low red light emission efficiency in the existing technology is solved, and stronger red light emission and wider application are achieved prospect.

CN119242305AInactive Publication Date: 2025-01-03HENAN HONCHOO TECH LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411330338.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2025-01-03
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The red light emission efficiency of existing rare earth doped upconverting materials is inefficient, making it difficult to achieve optimal biofluorescent labeling and bioimaging in the field of biomedical science.

Method used

By doping manganese ions in barium scandium aluminate, Ba2-xMnxSc0.67Yb0.3Er0.03AlO5 material is formed, and the doping concentration of manganese ions is regulated to improve the sensitization and emission ability of rare earth ions and enhance red light emission.

Benefits of technology

The intensity of red light emitted by manganese ion doped materials under 980nm laser irradiation has increased by 27.4 times, and is suitable for biomedical, new energy and solar cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119242305A_ABST
    Figure CN119242305A_ABST
Patent Text Reader

Abstract

The invention discloses manganese ion doped enhanced up-conversion red light emitting scandium aluminate and a synthesis method thereof, and belongs to the technical field of up-conversion luminescent materials. The molecular formula of the up-conversion luminescent material provided by the invention is Ba (2-x) MnxSc (0.67) Yb (0.3) Er (0.03) AlO5 (x = 0-0.5), and the preparation method is a high-temperature solid phase method. The radius of manganese ions is much smaller than that of barium ions, so that the manganese ions easily enter a main substrate Ba2ScAlO5 and influence a crystal field, and oxygen vacancies are generated in the material. Defects formed by the oxygen vacancies can increase the energy transfer efficiency of the material, so that the sensitization and emission capabilities of rare earth ions are improved, and the luminescence characteristic of the material is improved. The obtained Ba1. 6Mn0. 4Sc0. 67Yb0. 3Er0. 03AlO5 has the maximum red light emission intensity at the red light wavelength of 664nm under the excitation of 980nm near infrared laser, and compared with the red light emission intensity of Ba2Sc0. 67Yb0. 3Er0. 03AlO5 obtained in a contrast, the red light emission intensity of the Ba1. 6Mn0. 4Sc0. 67Yb0. 3Er0. 03AlO5 is improved by nearly 27.4 times. The manganese ion doped scandium barium aluminate up-conversion luminescent material prepared by the invention has excellent single red up-conversion luminescence, and meanwhile, the preparation method is simple, good in controllability, high in yield and more energy-saving and environment-friendly in preparation process, and is suitable for industrial popularization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of up-conversion luminescent materials, and in particular relates to a manganese ion-doped enhanced up-conversion red light luminescent scandium aluminate and a synthesis method thereof. Background Art

[0002] With the development of laser technology and nanotechnology, rare earth-doped upconversion materials have inestimable potential value in three-dimensional display, solar cells, bioimaging and biotherapy. In the research of upconversion nanomaterials, rare earth-doped nanocrystal materials are the most widely used. Compared with the instability and high photobleaching rate of organic dyes, the microtoxicity and non-specific binding interference of quantum dot materials, rare earth-doped upconversion fluorescent materials have the advantages of high optical stability, low biological toxicity and low photobleaching rate, which makes the research of rare earth-doped upconversion materials in the biomedical field gradually become a hot topic.

[0003] The luminescence spectrum of rare earth-doped upconversion nanomaterials is extremely rich, but there are some high-energy upconversion photons, which will have a certain impact on biological cells to a greater or lesser extent. In order to obtain the best biofluorescence labeling and bioimaging, it is necessary to limit the spectrum of rare earth ion-doped upconversion materials to the "biological window" (600~1100nm), and to obtain strong emission fluorescence. A large number of experiments by our research group have shown that rare earth-doped barium aluminate (Ba2Sc) can be irradiated with 980 nm laser. 0.67 Yb 0.3 Er 0.03 AlO5) can obtain a strong red light of 664 nm, so we believe that this upconversion fluorescent material can be used in biological probes, biotherapy and bioimaging.

[0004] Common methods for preparing scandium aluminate mainly include high-temperature solid-phase method, coprecipitation method, sol-gel method, etc. The preparation method of upconversion luminescent materials is roughly the same. The high-temperature solid-phase method is to mechanically stir and dry raw materials such as barium carbonate, antioxidant, and aluminum oxide, press the powder into sheets, and then calcine at high temperature to obtain the desired product. This method is widely used in various fields due to its advantages such as simple process, high controllability, and short synthesis cycle.

[0005] To further regulate and enhance (Ba2Sc 0.67 Yb 0.3 Er 0.03 AlO5) upconversion material, the present invention also uses a high temperature solid phase method to propose a method for doping a certain proportion of manganese ions (Ba 2-x Mn x Sc 0.67 Yb 0.3 Er 0.03AlO5) scandium aluminum barium compound, under 980nm near-infrared laser irradiation, the material emits more than Ba2Sc 0.67 Yb 0.3 Er 0.03 The stronger red light (664 nm) of AlO5 provides a new material for the application of upconversion fluorescent materials in biomedicine. Summary of the invention

[0006] The present invention aims at the technical problems of low red light emission efficiency of up-conversion luminescent materials in the above-mentioned prior art. The present invention proposes a manganese ion-doped up-conversion strong red light emitting material and a preparation method thereof. By adjusting the doping concentration of manganese ions and forming defects, the sensitization and emission ability of rare earth ions in the matrix material are improved, so that it emits stronger red light.

[0007] The technical solution adopted by the present invention is as follows: A manganese ion doped scandium aluminate for enhanced upconversion red light emission and a synthesis method thereof are provided, wherein the structural formula of the upconversion luminescent material is: Ba 2-x Mn x Sc 0.67 Yb 0.3 Er 0.03 AlO5( x = 0 - 0.5).

[0008] A manganese ion doped enhanced up-conversion red light emitting scandium aluminate and a synthesis method thereof are provided, characterized in that the method comprises the following steps: Step 1: Considering that barium ions are prone to evaporate during sintering, 10 wt.% more barium carbonate should be weighed. Therefore, according to the molar ratio of elements Ba, Mn, Sc, Yb, Er, and Al (2.2-1.1 x ): x Weigh barium carbonate, manganese oxide, scandium oxide, ytterbium oxide, erbium oxide and aluminum hydroxide as raw materials in a ratio of 0.67:0.3:0.03:1; Step 2: Pour the raw materials weighed in step 1 into a clean 50 mL beaker, add anhydrous ethanol, and stir thoroughly with a magnetic stirrer to obtain a uniform suspension; Step 3: The suspension is allowed to stand until the clear liquid and the precipitate are separated, and then dried to completely evaporate the anhydrous ethanol in the beaker to obtain a powder raw material; Step 4: Press the uniform raw material dried in step 3 into a round sheet; Step 5: Place the disc-shaped sample pressed in step 3 into a high-temperature muffle furnace, pre-calcine it at 1200°C for 25 minutes, then raise the temperature to 1500°C~1700°C and sinter for 1.5 hours. After naturally cooling to room temperature, take out the sample, grind it into powder, and obtain the target product.

[0009] The beneficial effects of the present invention are: 1. The present invention is based on Ba2Sc 0.67 Yb 0.3 Er 0.03 AlO5 upconversion material is doped with manganese ions to obtain a manganese ion-doped enhanced upconversion red light emitting material Ba 2-x Mn x Sc 0.67 Yb 0.3 Er 0.03 AlO5( x = 0 - 0.5). Since the radius of manganese ions is much smaller than that of barium ions, manganese ions can easily enter the main matrix Ba2ScAlO5 and affect the crystal field, causing oxygen vacancies in the material. The defects formed by these oxygen vacancies can increase the energy transfer efficiency of the material, thereby improving the sensitization and emission ability of rare earth ions and enhancing the luminescence properties of the material. 2. Compared with Ba2Sc without manganese ion doping 0.67 Yb 0.3 Er 0.03 AlO5 up-conversion luminescent material, Ba 1.6 Mn 0.4 Sc 0.67 Yb 0.3 Er 0.03 The relative intensity of the 664 nm red light excited by the AlO5 upconversion material is about 27.4 times higher; 3. Ba2Sc obtained by the present invention 0.67 Yb 0.3 Er 0.03 AlO5 upconversion materials can control the red light emission intensity by adjusting the concentration of doped manganese ions, and have great applications in biomedicine, new energy hydrogen production and solar cells.

[0010] 4. Ba of the present invention 1.6 Mn 0.4 Sc 0.67 Yb 0.3 Er 0.03 The synthesis method of AlO5 upconversion material is simple, high in yield, energy-saving and environmentally friendly, and suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 For Ba 2-x Mn x Sc 0.67 Yb 0.3 Er 0.03 AlO5( x = 0 - 0.5) series of powder X-ray diffraction spectra; Figure 2 Ba is excited by near-infrared 980nm laser. 2-x Mn x Sc 0.67 Yb 0.3 Er 0.03 AlO5( x = 0 - 0.5) series of up-conversion fluorescence spectra; Figure 3 Ba2Sc obtained in comparative example 0.67 Yb 0.3 Er 0.03 AlO5( x = 0) powder X-ray diffraction spectrum; Figure 4 Ba2Sc obtained in comparative example 0.67 Yb 0.3 Er 0.03 Upconversion fluorescence spectrum of AlO5 under near-infrared 980nm laser excitation; Figure 5 Ba obtained in Example 1 1.8 Mn 0.2 Sc 0.67 Yb 0.3 Er 0.03 AlO5( x = 0.2) powder X-ray diffraction spectrum; Figure 6 Ba obtained in Example 1 1.8 Mn 0.2 Sc 0.67 Yb 0.3 Er 0.03 Upconversion fluorescence spectrum of AlO5 under near-infrared 980nm laser excitation; Figure 7 Ba obtained in Example 2 1.6 Mn 0.4 Sc 0.67 Yb 0.3 Er 0.03 AlO5( x = 0.4) powder X-ray diffraction spectrum; Figure 8 Ba obtained in Example 2 1.6 Mn 0.4 Sc 0.67 Yb 0.3 Er 0.03 Upconversion fluorescence spectrum of AlO5 under near-infrared 980nm laser excitation; Fig. 9 Ba2Sc obtained in comparative example and example 2 0.67 Yb0.3 Er 0.03 AlO5( x = 0) and Ba 1.6 Mn 0.4 Sc 0.67 Yb 0.3 Er 0.03 AlO5( x = 0.4) absorption spectrum; Fig.10 Ba obtained in Example 3 1.5 Mn 0.5 Sc 0.67 Yb 0.3 Er 0.03 AlO5( x = 0.5) powder X-ray diffraction spectrum; Fig.11 Ba obtained in Example 3 1.5 Mn 0.5 Sc 0.67 Yb 0.3 Er 0.03 Upconversion fluorescence spectrum of AlO5 under near-infrared 980nm laser excitation. DETAILED DESCRIPTION

[0012] In order to make the objectives, technical solutions and advantages of the present invention more clear, the present invention is further described in conjunction with the following specific embodiments and with reference to the accompanying drawings.

[0013] Comparative Example: This comparative example prepares upconversion fluorescent Ba2Sc 0.67 Yb 0.3 Er 0.03 AlO5 samples are used to enhance the up-conversion red light emitting material Ba by doping it with different concentrations of manganese ions. 2-x Mn x Sc 0.67 Yb 0.3 Er 0.03 AlO5( x = 0 -0.5) for comparison, the specific preparation steps are as follows: Step 1: Calculate the required amount of raw materials according to the ratio, and weigh 0.01672 mol of barium carbonate, 0.00255 mol of scandium oxide, 0.00114 mol of ytterbium oxide, 0.00011 mol of erbium oxide, and 0.00760 mol of aluminum hydroxide respectively; Step 2: Pour all the raw materials weighed in step 1 into a 50 mL beaker, add 35 mL of anhydrous ethanol, and stir thoroughly with a magnetic stirrer for 60 min to obtain a uniformly mixed suspension; Step 3: After the suspension obtained in step 2 is allowed to stand for 25 minutes, it is placed in a forced air drying oven and dried at 60° C. for 15 hours to completely evaporate the anhydrous ethanol in the beaker to obtain a dry mixed raw material; Step 4: The mixed raw material obtained in step 3 is pressed into a disc with a thickness of 2 to 3 mm and a diameter of about 1.2 cm using a tablet press. During the pressing process, the pressure should be maintained at 20 MPa for 25 minutes to ensure close contact of the sample; Step 5: Place the pressed disc in step 4 into a molybdenum metal crucible and place it in a hydrogen furnace. First, evacuate the vacuum with a vacuum pump, and then purge it with hydrogen once or twice to ensure that the furnace is full of hydrogen. Then heat the hydrogen furnace to 1200°C and keep it for 25 minutes to ensure that each component raw material is decomposed into the corresponding oxide. Then heat it to 1700°C and keep it for 90 minutes. After completion, cool it naturally to room temperature, take out the sample, and grind it into fine powder with an agate grinding cup to obtain upconversion fluorescent Ba2Sc 0.67 Yb 0.3 Er 0.03 AlO5 samples.

[0014] Depend on Figure 3 The XRD results show that the obtained Ba2Sc 0.67 Yb 0.3 Er 0.03 The X-ray diffraction spectrum of AlO5 is completely consistent with the standard diffraction spectrum of Ba2ScAlO5 (PDF#43-0078), indicating that the obtained Ba2Sc 0.67 Yb 0.3 Er 0.03 AlO5 is a single-phase Ba2ScAlO5 upconversion fluorescent material. Figure 4 It can be seen from the fluorescence graph that under the near-infrared 980nm laser excitation, the Ba2Sc 0.67 Yb 0.3 Er 0.03 AlO5 emits red light at 664nm. Example

[0015] In this example, a manganese ion doped enhanced up-conversion red light emitting material Ba was prepared. 1.8 Mn 0.2 Sc 0.67 Yb 0.3 Er 0.03 AlO5( x = 0.2), the specific preparation steps are as follows: Step 1: Calculate the required amount of each raw material according to the molar ratio of Ba, Mn, Sc, Yb, Er, and Al of 1.98:0.2:0.67:0.3:0.03:1, and weigh 0.01505 mol of barium carbonate, 0.00152 mol of manganese oxide, 0.00255 mol of scandium oxide, 0.00114 mol of ytterbium oxide, 0.00011 mol of erbium oxide, and 0.00760 mol of aluminum hydroxide; Step 2: Pour all the raw materials weighed in step 1 into a 50 mL beaker, add 35 mL of anhydrous ethanol, and stir thoroughly with a magnetic stirrer for 60 min to obtain a uniformly mixed suspension; Step 3: After the suspension obtained in step 2 is allowed to stand for 25 minutes, it is placed in a forced air drying oven and dried at 60° C. for 15 hours to completely evaporate the anhydrous ethanol in the beaker to obtain a dry mixed raw material; Step 4: The mixed raw material obtained in step 3 is pressed into a disc with a thickness of 2 to 3 mm and a diameter of about 1.2 cm using a tablet press. During the pressing process, the pressure should be maintained at 20 MPa for 25 minutes to ensure close contact of the sample; Step 5: Place the pressed disc in step 4 into a molybdenum metal crucible, and then place it in a hydrogen furnace. First, evacuate the vacuum with a vacuum pump, and then purge it with hydrogen once or twice to ensure that the furnace is full of hydrogen; then heat the hydrogen furnace to 1200°C and keep it for 25 minutes to ensure that each component raw material is decomposed into the corresponding oxide; then heat it to 1700°C and keep it for 90 minutes. After completion, naturally cool it to room temperature, take out the sample, and use an agate grinding cup to fully grind the sample into fine powder to obtain the manganese ion doped enhanced up-conversion red light emitting material Ba 1.8 Mn 0.2 Sc 0.67 Yb 0.3 Er 0.03 AlO5.

[0016] pass Figure 5 The X-ray diffraction spectrum of Ba 1.8 Mn 0.2 Sc 0.67 Yb 0.3 Er 0.03 The phase of AlO5 conforms to the crystal structure of Ba2ScAlO5 (PDF#43-0078), indicating that Ba 1.8 Mn 0.2 Sc 0.67 Yb 0.3 Er 0.03 AlO5 is also a single-phase Ba2ScAlO5 with a hexagonal phase, indicating that manganese ions with x=0.2 are successfully incorporated into the Ba2ScAlO5 crystal without changing the crystal structure.

[0017] like Figure 4 , 6 As shown, the Ba obtained in this embodiment 1.8 Mn 0.2 Sc 0.67 Yb 0.3 Er 0.03 AlO5 and Ba2Sc obtained in comparative example 0.67 Yb 0.3 Er 0.03 By comparing the fluorescence spectrum of AlO5, it can be seen that under the same 980nm near-infrared laser excitation, Ba 1.8 Mn 0.2 Sc 0.67 Yb 0.3 Er 0.03 The emission intensity of 664nm red light emitted by AlO5 increased by nearly 1.59 times. Example

[0018] In this embodiment, the method of the above embodiment 1 is used to prepare the manganese ion doped enhanced up-conversion red light emitting material Ba 1.6 Mn 0.4 Sc 0.67 Yb 0.3 Er 0.03 AlO5( x = 0.4), the only difference is the weight of manganese oxide and barium carbonate, specifically: weigh 0.01338mol barium carbonate, 0.00304mol manganese oxide, 0.00255mol scandium oxide, 0.00114mol ytterbium oxide, 0.00011mol erbium oxide and 0.00760mol aluminum hydroxide; other steps remain unchanged. Finally, the manganese ion doped enhanced up-conversion red light emitting material Ba 1.6 Mn 0.4 Sc 0.67 Yb 0.3 Er 0.03 AlO5. The purpose is to further increase the doping ratio of manganese ions, hoping to obtain the optimal manganese ion doping ratio.

[0019] Figure 7 The XRD pattern of the obtained Ba 1.6 Mn 0.4 Sc 0.67 Yb 0.3 Er 0.03 The phase of AlO5 is consistent with the Ba2ScAlO5 crystal structure (PDF#43-0078), indicating that the product is a single-phase Ba2ScAlO5 with a hexagonal phase. 1.6 Mn 0.4 Sc 0.67 Yb 0.3 Er 0.03 AlO5.

[0020] At the same time, by Figure 4 , 8 From the fluorescence spectrum of Ba 1.6 Mn 0.4 Sc 0.67 Yb 0.3 Er 0.03 AlO5 has the maximum red light emission intensity at the red light wavelength of 664nm, which is higher than that of Ba2Sc obtained in the comparative example. 0.67 Yb 0.3 Er 0.03 The red light emission intensity of AlO5 increased by nearly 27.4 times.

[0021] Depend on Fig. 9 The absorption spectrum of Ba 1.6 Mn 0.4 Sc 0.67 Yb 0.3 Er 0.03 AlO5 has a wide absorption band near 640nm. Since the radius of manganese ions is much smaller than that of barium ions, manganese ions can easily enter the main matrix Ba2ScAlO5 and affect the crystal field, causing oxygen vacancies in the material. The defects formed by these oxygen vacancies can increase the energy transfer efficiency of the material, thereby improving the sensitization and emission capabilities of rare earth ions and enhancing the luminescence properties of the material. Example

[0022] In this embodiment, the method of the above embodiment 1 is used to prepare the manganese ion doped enhanced up-conversion red light emitting material Ba 1.5 Mn 0.5 Sc 0.67 Yb 0.3 Er 0.03 AlO5( x = 0.5), the only difference is the weight of manganese oxide and barium carbonate, specifically: weigh 0.01254mol barium carbonate, 0.00380mol manganese oxide, 0.00255mol scandium oxide, 0.00114mol ytterbium oxide, 0.00011mol erbium oxide and 0.00760mol aluminum hydroxide; other steps remain unchanged. Finally, the manganese ion doped enhanced up-conversion red light emitting material Ba 1.5 Mn 0.5 Sc 0.67 Yb 0.3 Er 0.03 The purpose is to verify whether there is a maximum value of the manganese ion doping ratio compared with Example 2.

[0023] Fig.10The XRD diffraction spectrum of the obtained Ba 1.5 Mn 0.5 Sc 0.67 Yb 0.3 Er 0.03 The crystal structure of AlO5 is consistent with the Ba2ScAlO5 crystal structure (PDF#43-0078).

[0024] Depend on Figure 8 , 11 The fluorescence spectrum shown in the figure shows that under the excitation of 980nm infrared laser, the obtained Ba 1.5 Mn 0.5 Sc 0.67 Yb 0.3 Er 0.03 The red light emission intensity of AlO5 at 664nm is compared with that of BaO2 obtained in Example 2. 1.6 Mn 0.4 Sc 0.67 Yb 0.3 Er 0.03 AlO5 has a significant decrease, which verifies that the manganese ion doping in this embodiment is excessive. Although the physical phase remains basically unchanged, the fluorescence quenching phenomenon occurs due to the high concentration of doping.

Claims

1. A manganese ion doped enhanced up-conversion red light emitting scandium aluminate and a synthesis method thereof, characterized in that: The structural formula of the up-conversion luminescent material is: Ba 2-x Mn x Sc 0.67 Yb 0.3 Er 0.03 AlO5( x = 0 - 0.5).

2. The manganese ion doped enhanced up-conversion red light emitting scandium aluminate and its synthesis method according to claim 1, characterized in that: The up-conversion phosphor Ba 1.6 Mn 0.4 Sc 0.67 Yb 0.3 Er 0.03 When AlO5 is doped with manganese ions, the defects formed by oxygen vacancies have the behavior of enhancing red light emission.

3. A manganese ion doped enhanced up-conversion red light emitting scandium aluminate and a synthesis method thereof, characterized in that: The following steps are involved: Step 1: According to the molar ratio of elements Ba, Mn, Sc, Yb, Er, Al (2.2-1.1 x ): x Barium carbonate, manganese oxide, scandium oxide, ytterbium oxide, erbium oxide and aluminum hydroxide are weighed as raw materials in a ratio of 0.67:0.3:0.03:1; wherein, x = 0, 0.1, 0.2, 0.3, 0.4, 0.5; Step 2: Pour all the raw materials weighed in step 1 into a beaker, add anhydrous ethanol, and stir to obtain a suspension; Step 3: Allow the suspension obtained in step 2 to stand until the supernatant and the precipitate are separated, and then dry until the anhydrous ethanol is completely evaporated to obtain a mixed raw material; Step 4: Press the mixed raw material obtained in step 3 into a round piece; Step 5: Place the wafer obtained in step 4 in a hydrogen furnace, first heat it to 1200°C and keep it for 10 to 40 minutes, then heat it to 1500 to 1700°C and keep it for 50 to 90 minutes. After completion, naturally cool it to room temperature, take out the sample, grind it into powder, and obtain a manganese ion doped enhanced up-conversion red light emitting material.

4. The method for preparing the upconversion phosphor with defect-enhanced red light emission behavior according to claim 3, characterized in that: The concentration of the suspension obtained in step 2 is 0.1 to 0.2 g of raw material per ml of anhydrous ethanol.

5. The method for preparing the upconversion phosphor with defect-enhanced red light emission behavior according to claim 3, characterized in that: In step 3, the drying temperature is set between 40 and 80° C., and the drying time is set between 5 and 12 hours.